Comparative evaluation of winter forage legumes under Mediterranean rain-fed conditions - Zigouraki A.; Chatzigeorgiou T.; Hadjigeorgiou I. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Forage production of adequate quantity of the proper quality is a timeless goal for ruminant production farming systems. Climatic conditions in semi-arid Mediterranean areas set a limit to this goal. With the aim to evaluate a range of forage legumes a trial was set up at the Agricultural University of Athens, where seeds were sown in a randomized design with two replicates. Forage species sown were: Trifolium spumosum (cv Bartolo), Trifolium hirtum (cv Hykon), Trifolium dasyurum (cv Sothis), Trifolium glanduliferum (cv Prima), Trifolium michelianum (cv Paradana), Trifolium subterraneum (Dalkeith), Biserulla pelecinus (Cashbah), Ornithopus sativus (Margurita), Ornithopus compressus (Santorini) Medicago polymorpha (Cavalier, Scimitar), Medicago littoralis (Angel). Quantity and quality characteristics (ash, crude protein, crude fiber as well as NDF and ADF contents) of the forage produced were recorded. It was observed that M. polymorpha (Scimitar) and Trifolium dasyurum (cv Sothis) were the most competitive against weeds and productive in forage DM, while nutritional characteristics were similar between species. It was concluded that productivity and competitiveness of a forage species (or cultivar) is a crucial factor for the production of rain-fed forage material of adequate quality under Mediterranean conditions.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)